Unravelling The Function of Derivational Affixes Found in BBC News “War in Ukraine” - Dewa Gede Agung Ambara; Ni Putu Cahyani Putri Utami (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
The study of word that focus on learning how the word is made by a combination of one or more morpheme is also known as Morphology. This study aims to discover the types and function of derivational affixes found in the BBC News “War in Ukraine”. This research applied two methods such as descriptive qualitative method to provide a comprehensive explanation to each data found in the research and quantitative method used to showcase the frequency percentages of various types and functions of derivational affixes discovered from the data source. Multiple BBC News “War in Ukraine” that contains numerous derivational affixes phenomenon has been chosen to conduct this study. Based on the analysis, this study found 139 (66%) data noun derived from verb, 9 (4%) data adjective derived from verb, 2 (1%) data verb derived from noun, 17 (9%) data adjective derived from noun, 8 (4%) noun derived from adjective, 32 (15%) adverb derived from adjective. Those data found from the research emphasize that forming nouns through derivational affixes is a relatively straightforward process, making it the most prevalent type of data in the study.